Gastrodin Attenuates Bilateral Common Carotid Artery Occlusion-Induced Cognitive Deficits via Regulating Aβ-Related Proteins and Reducing Autophagy and Apoptosis in Rats - Liu, Bo; Gao, Jian-Mei; Li, Fei; Gong, Qi-Hai; Shi, Jing-Shan (Frontiers in Pharmacology, 2018)
Gastrodin, an active constituent extracted from Gastrodia elata Blume, is used to treat ischemic stroke, epilepsy, dizziness and dementia for centuries in China. This study examined its effects on vascular dementia and the underlying molecular mechanisms.Vascular dementia was established by ligation of bilateral common carotid arteries (BCCAO). Seven days after BCCAO surgery, Gastrodin (15, 30, and 60 mg/kg) was orally administered for 28 consecutive days to evaluate therapeutic effects. Cognitive function was tested by the Morris water maze (MWM). The neuronal morphological changes were examined via HE staining. Flow cytometry was used for evaluating apoptosis in the hippocampi. The target protein expression was examined by Western-blot. The results showed that BCCAO induced cognitive impairment, hippocampus CA1 and CA3 pyramidal neuron damage, Aβ deposition, excessive autophagy and apoptosis. Gastrodin treatment significantly improved BCCAO-induced cognitive deficits and hippocampus neuron damage. Molecular analysis revealed that Gastrodin exerted the protective effect via reducing the levels of Aβ1–40/42, APP and β-site APP-cleaving enzyme 1 (BACE1) expression, and increasing Aβ-related protein, a disintegrin and metalloprotease 10 (ADAM10) and insulin degrading enzyme (IDE) expression. Meanwhile, Gastrodin inhibited excessive autophagy via decreasing Beclin-1, LC3-II, and p62 levels. Furthermore, Gastrodin inhibited apoptosis through the down-regulation of Bax and up-regulation of Bcl-2. Moreover, P38 MAPK signaling pathway was involved in the process. Our findings demonstrate that Gastrodin was effective in the treatment of BCCAO-induced vascular dementia via targeting Aβ-related protein formation and inhibiting autophagy and apoptosis of hippocampus neurons.